Stochastic modelling of bioethanol fermentation by Saccharomyces Cerevisiae grown in oil palm residues [electronic resource] - Mohd. Dinie Muhaimin Samsudin; Universiti Sains Malaysia
Thesis (Ph.D) - Universiti Sains Malaysia, 2015